2011
DOI: 10.1002/ana.22235
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing allows for rapid gene identification in a Charcot‐Marie‐Tooth family

Abstract: Objective Charcot-Marie-Tooth (CMT) disease comprises a large number of genetically distinct forms of inherited peripheral neuropathies. The relative uniform phenotypes in many patients with CMT make it difficult to decide which of the over 35 known CMT genes are affected in a given patient. Genetic testing decision trees are therefore broadly based on a small number of major subtypes (eg, CMT1, CMT2) and the observed mutation frequency for CMT genes. Since conventional genetic testing is expensive many rare g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 21 publications
3
71
0
2
Order By: Relevance
“…31,[33][34][35] In our study, we showed that the coverage of a predefined list of genes associated with dHMN and overlapping disorders was sufficiently high to use exome sequencing as an initial diagnostic approach. In addition, the combined use of Sequenom MassARRAY to validate the genetic variants identified appeared to be a fast and powerful strategy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…31,[33][34][35] In our study, we showed that the coverage of a predefined list of genes associated with dHMN and overlapping disorders was sufficiently high to use exome sequencing as an initial diagnostic approach. In addition, the combined use of Sequenom MassARRAY to validate the genetic variants identified appeared to be a fast and powerful strategy.…”
Section: Discussionmentioning
confidence: 85%
“…[27][28][29] More recently, the use of exome sequencing for diagnostic purposes in genetic disorders with a high degree of genetic heterogeneity such as CMT is being explored. 30,31 Although the prize of exome sequencing is declining, the bioinformatic tools for analysis have improved and the coverage of the sequencing appears to be sufficiently high for use in the diagnostic setting, several technical and ethical challenges remain. 32 In particular, establishing the pathogenicity of newly identified genetic variants is often difficult and the possibility of finding unrelated finding requires further attention.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Participants were asked to rate their response to: 'for me, learning such a result would be' by rating 1-7 on six items anchored by 'a bad thing-not a bad thing' , 'not beneficial-beneficial' , 'harmful-not harmful' , 'not a good thing-a good thing' , 'not worthwhileworthwhile' , 'unimportant-important' . Ratings were averaged and Cronbach alpha scores ranged from 0.88 to 0.96 for the four result categories.…”
Section: Methodsmentioning
confidence: 99%
“…Exome sequencing in particular has demonstrated its utility in the identification of causal genes in a variety of Mendelian disorders including ataxia [Montenegro et al, 2011;Ng et al, 2010;Pierson et al, 2011]. Although exome sequencing is a useful tool in new gene discovery, issues of cost and significant data storage burden associated with processing exome samples prohibit the routine use of sequencing in a diagnostic setting.…”
Section: Future Directions In Ataxia Research and Diagnosticsmentioning
confidence: 99%